Peranan aliran murji’ah dalam membangun Kehidupan toleransi di masa modern - Nurudin, Muhamad (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2017)
This paper explores the tolerance in the modern era. Tolerance is an important component in building a plural society aiming at living together without being distinguished from each other. Conversely, the lack of tolerance has the potential to threaten the unity especially in the context of the nation, like Indonesia. The awareness of diversity in thinking and acting will add harmonious life and tolerance, such as the Murji'ah group. This research used qualitative methods that are library research by using Islamic literature as the main reference. Therefore, it can be said that the difference in the world of Islamic thought has long been developed. It is in line with the teachings offered by the Murji'ah group. Although in its development this group is divided into two major groups namely the moderates (Mutawasith) and extreme (Mutasaddid). Since the Murji'ah no longer grew as a dynamic stream, but turned into a passive group. Nevertheless, the original character remains visible that is a tolerant attitude.